High-School Students Rarely Use E-Cigarettes Alone: A Sociodemographic Analysis of Polysubstance Use Among Adolescents in the United States. Issue 3 (13th February 2020) - Gilbert, Paul A; Kava, Christine M; Afifi, Rima
Abstract: Introduction: Most adolescents reporting e-cigarette use have also used combustible tobacco; however, the extent to which they use other substances is less clear. This study assessed e-cigarette use with tobacco, alcohol, or cannabis and quantified the risk of polysubstance use among adolescents overall and by sociodemographic characteristics. Aims and Methods: Using 2017 Youth Behavioral Risk Factor Surveillance System data from adolescents (grades 9–12) with complete substance use information ( n = 11 244), we examined e-cigarette poly-use status (none [referent], e-cigarettes only, or e-cigarettes + other substances). We estimated the prevalence of substance use and modeled odds of e-cigarette use, alone or with other substances, by several sociodemographic characteristics. Analyses were completed in Stata version 15.1 using survey procedures to account for the complex survey design. Results: Approximately 12% of adolescents reported past 30-day e-cigarette use. Almost all (93%) e-cigarette users also reported other substance use; alcohol appeared most frequently in combinations. Odds of e-cigarette single use and e-cigarette poly-use (vs. no use) were higher for males and adolescents with lower grades (odds ratios [ORs] = 1.44–2.31). Racial/ethnic minorities had lower odds of e-cigarette poly-use than White peers (ORs = 0.18–0.61), and bisexual (vs. straight) adolescents were more likely to be e-cigarette poly-users (OR = 1.62). E-cigarette use increased from 9th grade (7%) to 12th grade (16%). Conclusions: Polysubstance use is highly prevalent among adolescents who use e-cigarettes. Therefore, e-cigarette screening should include the assessment of other substances, especially alcohol. Early and comprehensive prevention efforts to reduce e-cigarette and other substance use could have a substantial beneficial impact on population health over time. Implications: This study extends knowledge about e-cigarette use among adolescents by exploring its use with alcohol, cannabis, and other tobacco products. We found that e-cigarettes were very rarely used alone, and our analysis identified several sociodemographic factors associated with greater odds of e-cigarette polysubstance use. In response, we recommend that prevention interventions address multiple substances concurrently, screen repeatedly to detect new initiation as age increases, focus on e-cigarette use as a less stigmatized entry point to discussions of substance use, and target priority population subgroups.